1983
DOI: 10.1620/tjem.139.43
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographical Diagnosis of Fatty Liver: Significance of the Liver-Kidney Contrast

Abstract: In order to investigate the reliability of ultrasonography in the diagnosis of fatty liver, retrospective evaluation was made of abdominal echograms in 45 patients with various diffuse liver diseases who underwent liver biopsy within 2 weeks after the ultrasound study. Instead of the well-recognized but subjective diagnostic criterion, i.e. the bright liver pattern, liver-kidney contrast is proposed as a new criterion. The liver-kidney contrast is based on the brightness of the liver in comparison to the renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
125
0
4

Year Published

1983
1983
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(131 citation statements)
references
References 2 publications
2
125
0
4
Order By: Relevance
“…23 Ultrasonography is a sensitive and reasonably accurate diagnostic tool for assessing fat infiltration of the liver. Others have found 83% sensitivity and 100% specificity in comparison with histology, and 100% sensitivity and 56% specificity in comparison with CT. 23,24 In this study, a second radiologist blindly reviewed 40 films originally classified as fatty liver and 80 films from age-and sex-matched persons that were not so classified. The positive agreement rate by the second rater was 80% and the negative agreement rate was 95%, yielding a kappa coefficient of agreement of 0.77.…”
Section: Baseline Data Collectionmentioning
confidence: 99%
“…23 Ultrasonography is a sensitive and reasonably accurate diagnostic tool for assessing fat infiltration of the liver. Others have found 83% sensitivity and 100% specificity in comparison with histology, and 100% sensitivity and 56% specificity in comparison with CT. 23,24 In this study, a second radiologist blindly reviewed 40 films originally classified as fatty liver and 80 films from age-and sex-matched persons that were not so classified. The positive agreement rate by the second rater was 80% and the negative agreement rate was 95%, yielding a kappa coefficient of agreement of 0.77.…”
Section: Baseline Data Collectionmentioning
confidence: 99%
“…Since histological workup is difficult to perform in order to make a diagnose, USG scanning can be used as the most practical and invasive method [10]. USG yields with a sensitivity of 83 % and a specificity of 100% [11]. In this study, the frequency of hepatosteatosis in inactive HBV carriers was found 68.7% which suggested an increased rate compared to the general population.…”
Section: Discussionmentioning
confidence: 56%
“…According to our ultrasound diagnostic criteria for the fatty liver (Yajima et al 1982b), a fatty change of about 50% of the area in the hepatic lobule was suspected (Fig. 1).…”
Section: Ultrasonographical Findingsmentioning
confidence: 99%
“…Moreover the influence of the thick abdominal wall must be taken into consideration and the advanced fibrosis of liver has been said to show bright liver pattern, too (Joseph et al 1979; Dewbury and Clark 1979). In the previous paper (Yajima et al 1982b), we proposed "liver-kidney contrast" which was defined as the relative brightness of the liver to the renal parenchyma where fatty change seldom occurs. In addition, it was also reported that combination of this liver-kidney contrast with two other well-known ultrasound findings of fatty liver, vascular blurring and deep attenuation, enabled us to grade fatty change semiquantitativel.y.…”
Section: Liver Histologymentioning
confidence: 99%
See 1 more Smart Citation